Metabolic control of daily locomotor activity mediated by tachykinin in Drosophila - Sang Hyuk Lee (Nature Portfolio, 2021)
Lee and colleagues report the effect of a high-sucrose diet on Drosophila locomotor activity via DTk-TkR86C neuropeptide signalling. This signalling pattern appears to involve a circadian element, with pacemaker neuron involvement having a possible time-of-day effect on locomotor behaviour.